1985
DOI: 10.1002/em.2860070509
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchanges in adult epileptic patients on phenytoin therapy

Abstract: Sister chromatid exchanges (SCE) were studied in lymphocyte cultures of 12 adult male epileptic patients on long-term monotherapy with phenytoin (PHT) and of matched controls. Significantly increased frequency of SCE was observed in the epileptic patients as a group and in almost all individuals, indicating a detectable chromosome damaging effect of PHT therapy on its human users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
2
10
1
Order By: Relevance
“…Kulkarni et al (1984) and Schaumann et al (1985) reported similar increases in SCE of 6 and 12 adult patients with epilepsy receiving PHT monotherapy, respectively. No difference between adult, PHT-treated patients and controls was observed by Sinues et al, however (1982).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Kulkarni et al (1984) and Schaumann et al (1985) reported similar increases in SCE of 6 and 12 adult patients with epilepsy receiving PHT monotherapy, respectively. No difference between adult, PHT-treated patients and controls was observed by Sinues et al, however (1982).…”
supporting
confidence: 57%
“…Among the in vivo studies of PHT-treated children with epilepsy, Hunke and Carpenter (1978) reported negative findings in 10 patients, and Habedank et al (1982) observed increased SCE frequencies in 9 patients as compared with healthy children. Kulkarni et al (1984) and Schaumann et al (1985) reported similar increases in SCE of 6 and 12 adult patients with epilepsy receiving PHT monotherapy, respectively. No difference between adult, PHT-treated patients and controls was observed by Sinues et al, however (1982).…”
mentioning
confidence: 73%
“…Guron et al (1985) and Schaumann et al (1985a) reported lack of SCE induction by CBZ. Concerning the in vivo studies of AED-treated epileptic individuals, Hunke and Carpenter (1978) failed to find a significant difference between SCE rates in epileptics treated with PHT and controls, whereas Habedank et al (1982) and Schaumann et al (1985b) observed increased SCE rates in child and adult patients with PHT monotherapy, respectively. Kulkarni et al (1984) reported a significant increase in SCE of epileptic patients treated PHT and/or PB as compared with controls.…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, in vivo studies of cell cycle analysis by Schaumann et al [11] did not reveal any significant difference between CBZ-treated patients and controls.…”
Section: Discussionmentioning
confidence: 95%
“…In vivo studies by Schaumann et al [11] showed no significant difference in cell cycle analysis between CBZ-treated patients and controls. The report by Goyle et al [12,13] provided a general assessment of mutagenicity in epileptic patients and emphasised the role of the disease in the higher occurrence of congenital malformations in their offspring.…”
Section: Introductionmentioning
confidence: 97%